P190 Ileo-caecal Crohn's Disease; medical or surgical management. Cost and outcomes. (27th May 2021) - Charan, M; Maclaren, L; Bryant, C; Wade, K; Johnson, H; McLaughlin, S
Abstract: Background: An ileo-caecectomy is known to be an effective treatment for Crohn's disease limited to the terminal ileum that can lead to a long term remission. ECCO guidelines recommend that patients with active inflammation should be treated medically. However the LIR!C trial suggested there are QOL benefits and reduced costs to performing primary surgery. Methods: We aimed to compare the outcomes of patients treated with primary medical treatment to primary surgery for patients with Crohn's disease limited to the terminal ileum. We reviewed our database to identify all these patients and analysed outcome data. Results: 49 patients were identified: Mean age was 50 yrs (range 22 - 93). 23 were male. Mean length of follow-up was 96 months (range 3 - 404). 1st line treatment was: medical; 33 (67.3%), surgery; 16 (32.6%). Outcomes after medical treatment: 27 of 33 patients failed primary medical treatment, they required surgery at a mean of 38 months (range 1–900) after initiating medical treatment. Colonoscopy after surgery to assess for disease recurrence: Colonoscopic assessment or calprotectin post was undertaken ileo-caecectomy in 4 of 16 patients at a mean of 6.2 months (range 1–10) who underwent primary surgery; and in 25 of 27 patients who underwent surgery following failure of medical treatment. Outcomes after surgery: 4 of 16 patients who had primary surgical treatment had endoscopic recurrence, requiring medical treatment after a mean of 4.4 months (range 0–10). 8 of 27 patients who had surgery post-failure of medical treatment developed disease recurrence, requiring medical treatment after a mean of 40 months (range 7–136) Bile acid malabsorption (BAM): BAM occurred after surgery in 10 of 43 patients. No medically managed patient developed BAM. Conclusion: These data suggest that in our population the vast majority of patients with ileo-caecal Crohn's disease will fail medical treatment and require surgery. 25% of those who undergo surgery will develop BAM (requiring medication), and 40% of those treated surgically will require immunosuppressant treatment in the medium term. These outcomes should be discussed with patients so that they appreciate that ileo-caecectomy is unlikely to lead to long term drug free treatment, and medical treatment is unlikely to lead to the avoidance of surgery. From a health-economics point of view it could be argued there is little point in offering primary medical therapy and ileo-caecectomy should be the initial treatment of choice for patients with limited ileo-caecal Crohn's disease. Unfortunately endoscopic/calprotectin assessment following primary surgery was often not performed in the majority of patients, and changes in our local practice need to be undertaken to correct this.